Red ginseng extract improves skeletal muscle energy metabolism and mitochondrial function in chronic fatigue mice - Zhang, Haijing; Zhao, Chunhui; Hou, Jinli; Su, Ping; Yang, Yifei; Xia, Bing; Zhao, Xiaoang; He, Rong; Wang, Lifang; Cao, Chunyu; Liu, Ting; Tian, Jixiang (Frontiers in Pharmacology, 2022)
Background: Skeletal muscles are organs with high energy requirements, especially during vigorous exercise. Adequate mitochondrial function is essential to meet the high energy needs of skeletal muscle cells. Recent studies have reported that red ginseng can significantly improve chronic fatigue; however, the specific mechanism of action is still not clear. Methods: A chronic fatigue syndrome mouse model was developed using C57BL/6J mice through long-term compound stimulation of stress factors. Following this, the animals were orally administered 200, 400, or 600 mg/kg red ginseng extracts for 28 days. Skeletal muscle lactate acid, serum lactate dehydrogenase, urea concentrations, ATP level, mitochondrial membrane potential, activities of Na+-K+-ATPase and cytochrome c oxidase were determined using assay kits or an automatic biochemical analyser detection system. Skeletal muscle mitochondria morphology was observed using electron microscopy and the expression of p-AMPK, PGC-1α, ACO2 and complex I in skeletal muscle protein was determined by western blotting. Results: Oral administration of 400 or 600 mg/kg red ginseng extract in mice with chronic fatigue reduced lactic acid, lactate dehydrogenase and urea, rescued the density and morphology of skeletal muscle mitochondria, increased the activities of Na+-K+-ATPase and cytochrome c oxidase, and activated the AMPK/PGC-1α cascade pathway, resulting in improved skeletal muscle mitochondrial function by restoring ATP level, mitochondrial membrane potential, complex I and mitochondrial biogenesis. Conclusion: The anti-fatigue effects of red ginseng are partly related to its potent mitochondrial improving activity, including decreasing mitochondrial swelling and mitochondrial membrane permeability, increasing mitochondrial biogenesis, thus ameliorating mitochondrial dysfunction.